Evaluation of the Association Between Genetic Variants in Circadian Rhythm Genes and Posttraumatic Stress Symptoms Identifies a Potential Functional Allele in the Transcription Factor TEF - Linnstaedt, Sarah D.; Pan, Yue; Mauck, Matthew C.; Sullivan, Jenyth; Zhou, Christine Y.; Jung, Lindsey; Rueckeis, Cathleen A.; Blount, Jameson D.; Carson, Matthew S.; Tungate, Andrew S.; Kurz, Michael C.; Hendry, Phyllis L.; et al. (Frontiers in Psychiatry, 2018)
Previous studies suggest that genetic variants within genes affecting the circadian rhythm influence the development of posttraumatic stress symptoms (PTSS). In the present study, we used data from three emergency care-based cohorts to search genetic variants in circadian pathway genes previously associated with neuropsychiatric disorders for variants that influence PTSS severity. The three cohorts used included a discovery cohort of African American men and women enrolled following motor vehicle collision (n=907) and two replication cohorts: one of multi-ethnic women enrolled following sexual assault (n=274) and one of multi-ethnic men and women enrolled following major thermal burn injury (n=68). DNA and RNA were collected from trauma survivors at the time of initial assessment. Validated questionnaires were used to assess peritraumatic distress severity and to assess PTSS severity six weeks, six months, and one year following trauma exposure. Thirty-one genetic variants from circadian rhythm genes were selected for analyses, and main effect and potential gene*stress and gene*sex interactions were evaluated. Secondary analyses assessed whether associated genetic variants affected mRNA expression levels. We found that six genetic variants across five circadian rhythm-associated genes predicted PTSS outcomes following motor vehicle collision (p<0.05), but only two of these variants survived adjustment for multiple comparisons (False Discovery Rate<5%). The strongest of these associations, an interaction between the PAR-zip transcription factor, thyrotroph embryonic factor (TEF) variant rs5758324 and peritraumatic distress, predicted PTSS development in all three cohorts. Further analysis of genetic variants in the genetic region surrounding TEFrs5758324 (±125,000 nucleotides) indicated that this allele showed the strongest association. Further, TEF RNA expression levels (determined via RNA-seq) were positively associated with PTSS severity in distressed individuals with at least one copy of the TEFrs5758324 minor allele. These results suggest that rs5758324 genetic variant in TEF, a regulator of clock-controlled genes and key mediator of the core circadian rhythm, influence PTSS severity in a stress-dependent manner.